2021
DOI: 10.1186/s13287-021-02500-9
|View full text |Cite
|
Sign up to set email alerts
|

MSCs from polytrauma patients: preliminary comparative study with MSCs from elective-surgery patients

Abstract: Background Polytrauma is a major clinical problem due to its impact on morbidity and mortality, especially among the younger population. Its pathophysiology is not completely elucidated, and the study of the involvement of certain cell populations with therapeutic potential, such as mesenchymal stromal cells (MSCs), is an area of growing interest, as mesenchymal cells have anti-inflammatory, immunoregulatory, and osteogenic potential. Methods In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In several conditions that may lead to SIRS, as polytrauma or infections, previous works (including ours), have shown that MSCs are activated by the abnormal microenvironment conditions (e.g. hypoxia, inflammatory and apoptotic signals), adapting their baseline properties to potentially restore the tissue homeostasis 48,49 . Activated MSCs can reduce the immune collateral damage by modulating the cytokine storm and immune overactivation.…”
Section: Mscs Immunomodulatory Potential In Sirsmentioning
confidence: 75%
See 1 more Smart Citation
“…In several conditions that may lead to SIRS, as polytrauma or infections, previous works (including ours), have shown that MSCs are activated by the abnormal microenvironment conditions (e.g. hypoxia, inflammatory and apoptotic signals), adapting their baseline properties to potentially restore the tissue homeostasis 48,49 . Activated MSCs can reduce the immune collateral damage by modulating the cytokine storm and immune overactivation.…”
Section: Mscs Immunomodulatory Potential In Sirsmentioning
confidence: 75%
“…hypoxia, inflammatory and apoptotic signals), adapting their baseline properties to potentially restore the tissue homeostasis. 48 , 49 Activated MSCs can reduce the immune collateral damage by modulating the cytokine storm and immune overactivation.…”
Section: Mscs Immunomodulatory Potential In Sirsmentioning
confidence: 99%